2004
DOI: 10.1176/appi.ajp.161.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation Measured With fMRI During a Mental Arithmetic Task in Schizophrenia and Major Depression

Abstract: A double dissociation of parietal and frontal lobe activation was found for the schizophrenia patients and the depression patients. The greater parietal lobe activation in the patients with schizophrenia may reflect a compensatory strategy for the failure to recruit cognitive processes that involve frontal lobe areas when solving a mental arithmetic task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
88
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 33 publications
11
88
0
5
Order By: Relevance
“…Past studies have suggested that when clinical populations (e.g. schizophrenia) are unable to behaviorally execute tasks, patterns of brain activation may represent compensatory mechanisms when they fail to successfully recruit brain regions necessary for cognitive tasks (Hugdahl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have suggested that when clinical populations (e.g. schizophrenia) are unable to behaviorally execute tasks, patterns of brain activation may represent compensatory mechanisms when they fail to successfully recruit brain regions necessary for cognitive tasks (Hugdahl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the relationship between affective symptoms and brain activation is one approach to understanding the underlying nature of affective symptoms in more depth. Many brain activation studies using a combination of brain images and cognitive tasks have helped reveal the neural basis of psychiatric disorders such as major depressive disorder (MDD) (Harvey et al, 2005;Hugdahl et al, 2004;Pu et al, 2008). Interestingly, most studies using a phonemic verbal fluency task (e.g., producing words that begin with a particular letter) showed hypoactivation of the prefrontal cortex in patients with MDD (Audenaert et al, 2002;Matsuo et al, 2002;E.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In contrast, MDD patients show abnormal activation patterns marked by more pronounced activation on the left prefrontal cortex and the cingulate cortex during working memory tasks. [25][26][27][28][29][30][31] However, all results are not consistent. Some studies suggest that patients with mood disorders show greater activation, 25,31 less activation [26][27][28] or no difference in activation within the regions of interest compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] However, all results are not consistent. Some studies suggest that patients with mood disorders show greater activation, 25,31 less activation [26][27][28] or no difference in activation within the regions of interest compared to healthy controls. 29,30 A functional magnetic resonance imaging (fMRI) study of MDD patients during an n-back task showed significantly lower activation in bilateral thalamus, right precentral gyrus and right parietal cortex compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation